Lin28/microRNA-let-7a promotes metastasis under circumstances of hyperactive Wnt signaling in esophageal squamous cell carcinoma - Ling, Rui (Mol Med Rep, 2018)
Dysregulation of micro (mi)RNA-let-7 has been associated with the development and prognosis of multiple cancer types. Lin28, a RNA-binding protein, plays a conserved role in regulating the maturation of let-7 family proteins. However, few studies have focused on the effects of Lin28/let-7 on Wnt-activated esophageal squamous cell carcinoma (ESCC). Analysis of the expression of let-7a, let-7b and let-7c in clinical tissues revealed that lower let-7a expression was correlated with higher tumor node metastasis staging and recurrence in patients with ESCC. Furthermore, it was demonstrated that let-7a was inversely correlated with the migration and invasion of ESCC cells. In addition, epithelial-mesenchymal transition, and the expression of VEGF-C and MMP9 were effectively decreased by let-7a-mimic or siRNA-Lin28 pretreatment. Mechanistically, Lin28 functioned as the key factor in signal transduction, which regulated the expression of let-7a and the downstream genes along the Wnt signaling pathway. Taken together, these findings identified a biochemical and functional association between Lin28/let-7a, and the Wnt pathway in ESCC cells.